2024
DOI: 10.3390/environments11040078
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Phthalates in Algae: Biosynthesis and Environmental Bioaccumulation

Andrea Pace,
Alessandro Vaglica,
Antonella Maccotta
et al.

Abstract: Phthalic acid esters (PAEs) are a class of ubiquitous and dangerous lipophilic chemicals widely used as additives in various products to improve their physical and chemical properties. Although they have been banned in many countries, their persistence in all environmental compartments is of particular concern. The aquatic environment is especially affected by these compounds because it is strongly influenced both by contamination of anthropic origin and natural contaminants including those produced biosynthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
(161 reference statements)
0
0
0
Order By: Relevance
“…For instance, pesticides play a crucial role in modern agriculture by combating biotic factors that pose threats to crops; organometallic compounds serve as antifouling agents in ship paints; biocides have been used in polymers, textiles, etc. ; TEs such as zinc and iron have been used as soil improvers; and PFAS and PAEs have been used as additives or constituents to improve the characteristics of different products, such as plastics and textiles [ 3 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, pesticides play a crucial role in modern agriculture by combating biotic factors that pose threats to crops; organometallic compounds serve as antifouling agents in ship paints; biocides have been used in polymers, textiles, etc. ; TEs such as zinc and iron have been used as soil improvers; and PFAS and PAEs have been used as additives or constituents to improve the characteristics of different products, such as plastics and textiles [ 3 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that aquatic organisms easily bioaccumulate these pollutants [ 4 , 5 , 6 , 7 , 8 , 11 , 12 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Among these, particular attention has recently been paid to Procambarus clarkii (Girard, 1852), an alien and invasive species widely recognized as a bioaccumulator of pollutants, particularly of toxic elements [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%